Effects of lifestyle modification counselling on weight and body composition among adults with overweight or obesity on antiretroviral therapy: a randomized controlled trial - Agete Tadewos Hirigo; Moges Derbe; Daniel Yilma; Ayalew Astatkie; Zelalem Debebe (Obesity Pillars)
Background: we aimed to evaluate the impact of lifestyle modification counselling on weight and body composition among adults with overweight or obesity receiving antiretroviral treatment (ART). Methods: This randomized, open-label, controlled trial enrolled 126 adults aged 18–65 years, living with human immunodeficiency virus (HIV) and classified as overweight or obese. Of these, 116 participants (63 in the control group and 53 in the intervention group) completed the six-month follow-up. Weight and body composition outcomes were analyzed among those who completed the study, with comparisons made between baseline and post-intervention measurements. The effect of lifestyle modification counselling on weight and body composition was evaluated through linear mixed effects model and multiple linear regression analysis. Results: Over the six-month trial, participants who received lifestyle modification counselling showed significantly greater reductions in body weight (Δ = −1.4 kg, p = 0.002), visceral fat (Δ = −0.53, p = 0.006), fat mass (Δ = −2.16 kg, p ​< ​0.001), and body fat percentage (Δ ​= ​−2.02 ​%, p ​< ​0.001) compared to the control group. The intervention group experienced greater increases in fat-free mass (Δ ​= ​+0.673 kg, p ​= ​0.068) and percentage skeletal muscle (Δ ​= ​+1.27 ​%, p ​< ​0.001) compared to the control group. Additionally, lifestyle modification counselling significantly contributed to achieving at least a 3 ​% weight loss from baseline (β ​= ​0.158, p ​= ​0.048). Conclusion: Lifestyle modification counselling resulted in promising and favorable changes in weight and body composition. Therefore, offering routine structured counselling interventions within ART clinics for individuals with overweight or obesity may help reduce obesity-related health risks and improve clinical outcomes (Thai Clinical Trials Registry TCTR20240905007).